Economic capital allocation with Basel II: cost, benefit and implementation procedures - Chorafas, Dimitris N. (Amsterdam: Elsevier, Butterworth Heinmann, 2004)
The discusses Basel II covering the evolution of the banking industry as it relates to Basel II; information on the capital requirements for bank liquidity and solvency; the new rules as laid down by the supervisory authorities of the Group of Ten industrialized nations; key information on the technical requirements for credit institutions such as: new credit rating scales, modeling of credit risk, control of operational risks, and, novel ways and means for the management of exposure to Credit Risk; Basel II accords must be implemented by 2006 and require 2 years preparation for proper implementation.
Commercial banks and the new regulation: Basel II, Impact Studies, and cost of implementation; Benefits from Basel II: Risk-based pricing and rating targets; Regulatory; Capital Defined; Market discipline and its global impact; The allocation of business capital to business units: Economic capital defined; Economic capital and solvency management; Economic capital allocation: practical applications and theoretical background; Evolving rules and procedures for economic capital allocation; Strategies used by banks to increase their capital base; Defaults, internal ratings and technological solutions: defined; IRB, technological infrastructure, models and correlations; Internal ratings, supervisory weights and collateral; Software which can help in IRB implementation; How to be in charge of IRB; Regulatory and political issues tend to be indivisable: Supervisory authorities and their regulatory policies; Supervisory authorities and their regulatory policies.
Includes bibliographical references and index.
lje 4/9/13 5/9/13
Keywords: Banks and banking -- State supervision; Risk management; Business & Economics